Can twitter be an effective platform for political discourse in Malaysia? A Study of #PRU13 - Kasmani, Mohd Faizal; Sabran, Rosidayu; Ramle, NorAdzrah (Elsevier Ltd., 2014)
Studies show that social media play an important role in shaping political discourse. Applications of Web 2.0, particularly Twitter, are currently influencing the nature of online participation in which the audience is not merely passively reading web content, but is actually contributing to and creating the content.This study examines communication on Twitter during the 13th Malaysian General Election based on Twitter messages collected under the #PRU13 hashtag.The analyzed dataset is collected from Twitter's public timeline from May 1 to May 6, 2013.This study found lack of diversity in the discussion on Twitter sphere in which tweets that are pro-Barisan National coalition dominates the #pru13. Based on the communication patterns, however, #PRU13 constitute a multifaceted group of commenters who seek to persuade, educate, provoke and so on.